Current Trends and Perspectives in the Immune Therapy for Substance Use Disorders - Vasiliu, Octavian (Frontiers in Psychiatry, 2022)
Substance use disorders (SUDs) are an extremely challenging category of disorders because of the high rate of relapse, lower life expectancy, important rate of psychiatric and somatic co-morbidity, lack of patients’ insight during most of the disease duration, healthcare costs, etc. One of the reasons to consider these disorders very difficult for physicians and the healthcare system is the lack of adequate pharmacological agents with long-term proven efficacy. So far, there are no Food and Drug Administration (FDA) or European Medicines Agency (EMA)-approved treatments for most of the SUDs, except for alcohol use disorder, nicotine use disorder, and opioid use disorder. Immunotherapy has been considered a possible solution to SUDs because it may selectively target a certain drug of abuse, it may have a long-lasting effect (several weeks or months), and it ensures an adequate therapeutic adherence. The objective of this paper was to establish the current stage of research in the field of SUDs vaccines, based on a brief literature review. Vaccines for cocaine and nicotine dependence have reached phase III trials, while other researchers are focusing on passive immunization therapy for methamphetamine use disorder. New generations of vaccines are currently explored, and they are based on superior technologies compared to the first generation of immune therapy (e.g., viral transfer genes, more immunogenic adjuvants, or higher specificity haptens). Therefore, finding immune therapies for substance use disorders SUDs remains a matter of interest, and this approach may be useful for the management of an extremely dangerous and versatile psychiatric pathology.